2008
DOI: 10.1111/j.1439-0523.2007.01464.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a major genetic factor conditioning freezing sensitivity in winter wheat

Abstract: The inheritance of freezing tolerance in F 2 -derived F 4 populations from all possible crosses of winter wheat cultivars ÔKestrelÕ, ÔEltanÕ, ÔTiberÕ, ÔFroidÕ and germplasm line Oregon Feed Wheat #5 (ORFW) was investigated. When frozen to a temperature equal to the LT 50 of the least freezing tolerant parent (ORFW), survival frequency distributions were skewed to greater survival in six of the 10 crosses, however, very few of the progeny from the four crosses to ORFW survived. The inheritance of this freezing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
4
16
0
Order By: Relevance
“…These clusters appear to represent groups of cultivars that employ somewhat diff erent combinations of mechanisms in their response to the various stresses imposed by the freezing process. This possibility is supported by previously published results (Skinner and Garland-Campbell, 2008). 1), the levels of freezing tolerance were very similar (Table 3), but the clear distinction of the clusters suggested that diff erent mechanisms were used in developing those similar levels of tolerance.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These clusters appear to represent groups of cultivars that employ somewhat diff erent combinations of mechanisms in their response to the various stresses imposed by the freezing process. This possibility is supported by previously published results (Skinner and Garland-Campbell, 2008). 1), the levels of freezing tolerance were very similar (Table 3), but the clear distinction of the clusters suggested that diff erent mechanisms were used in developing those similar levels of tolerance.…”
Section: Discussionsupporting
confidence: 84%
“…Among the cultivars comprising clusters 1 and 2 (Fig. 2 in Skinner and Garland-Campbell, 2008). For example, Froid and Kestrel expressed a level of freezing tolerance that was significantly greater than all other cultivars except Norstar (Table 3), yet Froid and Kestrel were grouped into diff erent clusters by their responses to the freezing process components (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Winter wheat cultivar Eltan (Peterson et al, 1991), spring wheat cultivar Louise (Kidwell et al, 2006), and germplasm line Oregon Feed Wheat #5 (described in DeNoma, 1990; Skinner and Garland‐Campbell, 2008) were used. Twenty seeds of each wheat line were planted into commercial soilless planting mix in each 3.8‐cm by 3.8‐cm by 6.3‐cm cell of a six‐cell insert in a horticultural growing tray (Model 806, Hummert, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the genetic architecture of frost tolerance has been investigated for almost a century (Skinner and Garland-Campbell, 2008; Galiba et al , 2009). One prominent frost tolerance locus is Fr-1 (Sutka and Snape, 1989; McIntosh et al , 1998), which maps close to Vrn-A1 and thus has been supposed to represent a pleiotropic effect of Vrn-A1 (Dhillon et al , 2010).…”
Section: Introductionmentioning
confidence: 99%